The Keyboard Sonatas of Joseph Haydn: Instruments and Performance Practice, Genres and Styles - Somfai, László 1934- (Chicago University of Chicago Press, 1995)
Interest in the authentic performance of early music has grown dramatically in recent years, and scholarly investigation has particularly benefited the study of keyboard music of the classical period. In this landmark publication, the most comprehensive study written on Haydn's keyboard sonatas, a leading Haydn scholar presents novel ideas, corrects misconceptions, and offers new hypotheses on long-debated issues of early music research.Laszlo Somfai begins with a thorough study of Haydn's keyboard instruments and their development. After recommending instruments appropriate for modern use, he discusses performance practice and style, explains the peculiarities of Haydn's manuscripts in the context of eighteenth-century notation, and provides specific suggestions for playing ornaments, improvising, slurring, and dynamics. He also investigates Haydn's sonata genres within their historical context and discusses the problems of establishing a chronology of their composition. Finally, Somfai analyzes the organization and style of each musical form. The book includes an index listing the sonatas by date of first publication, and an extensive bibliography.
Keywords: Haydn, Joseph -- 1732-1809; 18th Century (1701-1800); Sonata; Keyboard music; Keyboard instrument